2012
DOI: 10.1103/physrevb.85.235430
|View full text |Cite
|
Sign up to set email alerts
|

Doping domains in graphene on gold substrates: First-principles and scanning tunneling spectroscopy studies

Abstract: We have studied graphene/gold interface by means of density functional theory (DFT) and scanning tunneling spectroscopy (STS). Weak interaction between graphene and the underlying gold surface leaves unperturbed Dirac cones in the band-structure, but they can be shifted with respect to the Fermi level of the whole system, which results in effective doping of graphene. DFT calculations revealed that the interface is extremely sensitive to the adsorption distance and to the structure of metal's surface, in parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
(57 reference statements)
3
15
0
Order By: Relevance
“…This is consistent with previous reports for graphene exfoliated from graphite and transferred ex M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT situ to Au(111) [5], yet in contrast to the p-type doping reported for graphene grown in situ on Au(111) via vapor deposition [27]. This discrepancy may be related to a different adsorption distance [28] of the graphene on Au(111) in the different preparation approaches. Intercalation with water molecules, which occurs during ex situ transfer of the graphene, has been found to lead to a stronger n-type doping of graphene on Au(111) [5].…”
Section: Figures 4 (D)-(f) Presentsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous reports for graphene exfoliated from graphite and transferred ex M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT situ to Au(111) [5], yet in contrast to the p-type doping reported for graphene grown in situ on Au(111) via vapor deposition [27]. This discrepancy may be related to a different adsorption distance [28] of the graphene on Au(111) in the different preparation approaches. Intercalation with water molecules, which occurs during ex situ transfer of the graphene, has been found to lead to a stronger n-type doping of graphene on Au(111) [5].…”
Section: Figures 4 (D)-(f) Presentsupporting
confidence: 90%
“…Previously, graphene was grown on Au (111) by deposition of elemental carbon and subsequent annealing, yielding dendritic graphene islands [17] that eventually can evolve into quasi-single crystalline graphene films [27]. Compared to more rough, granular substrates [28], graphene on atomically flat substrates, either grown by CVD or obtained by transfer, is interesting for studies of doping with, e.g., nitrogen, as it allows to conveniently retrieve dopants using atomically resolved STM [9][10][11]30].…”
Section: Introductionmentioning
confidence: 99%
“…Overall the fit of this work describes also the calculated values (green open squares in figure 6) very well. The surfaces included in the fit all have a graphene-metal distance of around 3.4 Å [34][35][36][37][38]. The surfaces of Ni, Ru and Pd were not included in the fit and are shown by blue dashed circles.…”
Section: Work Functionmentioning
confidence: 99%
“…These contacts are made by sputtering or ebeam evaporation and consist of polycrystalline grains. The interaction of graphene with such a polycrystalline gold layer was investigated recently by transferring graphene flakes on a sputtered, 8 nm gold layer [22]. Based on STS measurements, it was concluded that the gold substrate is the mixture of (111) crystallites and amorphous-type regions.…”
Section: Introductionmentioning
confidence: 99%